Институциональные условия капитализации предприятий инновационно развитых стран Азиатско-Тихоокеанского региона - Фирсов, А.В. (Економіка промисловості, 2014)
Рассмотрены институциональные условия инновационного развития государства как основополагающей предпосылки процесса капитализации предприятий на примере стран АТР и Украины. Исследован опыт Японии и Ю. Кореи в«управлении» институциональными изменениями в целях капитализации промышленных предприятий. Определены основные характерные особенности, влияющие на изменение стоимости бизнеса, капитализации предприятий в азиатских странах. Розглянуто інституційні умови інноваційного розвитку держави як основної передумови процесу капіталізації підприємств на прикладі країн АТР і України. Досліджено досвід Японії та Пд. Кореї в «управлінні» інституціональними змінами з метою капіталізації промислових підприємств. Визначено основні характерні особливості, які впливають на зміну вартості бізнесу, капіталізації підприємств в азіатських країнах. The relevance of the study of Eastern directions of institutional context of enterprises capitalization is due to the high achievements in the development of the economies, societies, and states in the Asia-Pacific region (Australia, Indonesia, Canada, China, Mexico, Russia, USA, South Korea, Japan, etc). The study of Eastern vector will provide an opportunity to use theoretical and practical experience of the Asian countries in Ukraine in order to expand the variations of ideas for business development. Thus, the desire for dominance of competitive high-tech, innovative enterprises in the structure of Ukraine’s economy should rely on capitalization as one of the tools of business development. Therefore, it is expedient to consider international experience, especially its Eastern vector as a priority in institutional matters of enterprises capitalization. The main aim of the research is the analysis and generalization of the experience of the Asia-Pacific region in the institutional issues of enterprises capitalization with the possibility of its further use in Ukraine. In the article the institutional conditions of innovative development of a state as the fundamental prerequisite to the process of enterprises capitalization are considered on the basis of the Asia-Pacific region and Ukraine. The list of innovative development of countries in 2013 and the rating of the countries concerning the institutions that affect the innovation in the same period are given. The institutions affecting innovation in Ukraine and in the countries of the Asia-Pacific region are compared. The institutional potential of the countries of the Asia-Pacific region and Ukraine in innovation activity is identified. The experience of Japan and South Korea in the institutional changes "management" in order to capitalise the industrial enterprises is studied. The basic institutional conditions of functioning of "joint ventures" in Japan and South Korea are considered. The institutional comparison of Japan and South Korea is conducted. The important trend that affects the cost of business changes over time is identified. The main characteristic features that determine the processes of change of business value and enterprises capitalization in Asian countries are detected. The mechanism of capitalization of domestic enterprises is developed.